The "FCR" Approach to the Knee for the Management of Posterior Tibial Plateau Fractures. Issue 6 (June 2020) - Berwin, James T.; Donovan, Richard L.; Riddick, Andrew; Kelly, Michael B.
Abstract : Summary: Three-column fixation of tibial plateau fractures is now an established philosophy. A direct posterior approach with the patient prone affords enhanced exposure of the posterior column and ease of access for fixation using a buttress plate and posterior-to-anterior screws. A "direct posterior" approach through a reverse L-shaped incision to back of the knee is popular, yet complications associated with raising a fascial flap can occur. We present a simple method of conceptualizing a direct posterior approach through a single longitudinal incision, by likening it to a commonly performed orthopedic approach, the flexor carpi radialis approach to the wrist. Abstract : Supplemental Digital Content is Available in the Text.